Teacher Training Models in Higher Education, for a proposal from the Center for Teaching Improvement of the University of Atacama - Paredes Olivares, Marcela; Pedreros Gaete, Paola (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The University of Atacama (UDA) is a public and regional institution that, based on the process of curricular innovation that began in 2000 in Chile, creates the Center for Teacher Improvement (CMD), a unit in charge of teacher training. As of 2021, the CMD is evaluating its training actions to update its Training Model. By virtue of the foregoing, the revision of theoretical models of teacher training, current legislation and regulations, preparation of the teaching profile, among others, has been proposed. Here we expand and delve into the theoretical models of teacher education defined in the literature.